Hyperbolic equations in wavelet bases - Cattani, C.; Toscano, L. (Інститут гідромеханіки НАН України, 2000)
In this paper we discuss the problem of representing hyperbolic differential operators using orthonormal wavelet bases. A numerical algorithm is shortly outlined and a numerical experiment in the linear magnetohydrodynamics, as a test problem, is eventually outlined.